Immigration, Civil Rights & the Evolution of the People - Rodríguez, Cristina M. (Daedalus, 2013)
In considering what it means to treat immigration as a “civil rights” matter, I identify two frameworks for analysis. The first, universalistic in nature, emanates from personhood and promises non-citizens the protection of generally applicable laws and an important set of constitutional rights. The second seeks full incorporation for non-citizens into “the people,” a composite that evolves over time through social contestation – a process that can entail enforcement of legal norms but that revolves primarily around political argument. This pursuit of full membership for non-citizens implicates a reciprocal relationship between them and the body politic, and the interests of the polity help determine the contours of non-citizens' membership. Each of these frameworks has been shaped by the legal and political legacies of the civil rights movement itself, but the second formulation reveals how the pursuit of immigrant incorporation cannot be fully explained as a modern-day version of the civil rights struggle.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDAyMjk